2018
DOI: 10.1159/000490174
|View full text |Cite
|
Sign up to set email alerts
|

One Size Does Not Fit All: Comparative Diagnostic Accuracy of the Rowland Universal Dementia Assessment Scale and the Mini Mental State Examination in a Memory Clinic Population with Very Low Education

Abstract: Background: Diagnosing dementia in elderly immigrants is often difficult due to language and cultural barriers, low education, and illiteracy. We compared the diagnostic accuracy of the Rowland Universal Dementia Assessment Scale (RUDAS) to that of the Mini Mental State Examination (MMSE). Methods: A total of 144 patients (42 with intact cognition, 44 with mild cognitive impairment [MCI], and 58 with dementia) were administered both instruments and were diagnosed by specialists blinded for MMSE and RUDAS resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 54 publications
(73 reference statements)
4
35
1
Order By: Relevance
“…Additionally, three studies (Chen et al, 2015;Custodio et al, 2019; Matias-Guiu et al, 2017) did not report clearly on methods for patient selection, three (Cheung et al, 2015;Matias-Guiu et al, 2017;Nielsen et al, 2019c) on the interpretation of the RUDAS, four (Cheung et al, 2015;Nielsen et al, 2019c;Ramos-Ríosa et al, 2009;Shaaban et al, 2013) on the interpretation of the reference standard, and five (Cheung et al, 2015;Mateos-Alvarez et al, 2017;Matias-Guiu et al, 2017;Silpakit et al, 2018) on the flow and timing of the study. Applicability concerns were identified in three studies and were related to uncertain application of the RUDAS (Cheung et al, 2015;Custodio et al, 2019) or the reference standard (Goudsmit et al, 2018).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, three studies (Chen et al, 2015;Custodio et al, 2019; Matias-Guiu et al, 2017) did not report clearly on methods for patient selection, three (Cheung et al, 2015;Matias-Guiu et al, 2017;Nielsen et al, 2019c) on the interpretation of the RUDAS, four (Cheung et al, 2015;Nielsen et al, 2019c;Ramos-Ríosa et al, 2009;Shaaban et al, 2013) on the interpretation of the reference standard, and five (Cheung et al, 2015;Mateos-Alvarez et al, 2017;Matias-Guiu et al, 2017;Silpakit et al, 2018) on the flow and timing of the study. Applicability concerns were identified in three studies and were related to uncertain application of the RUDAS (Cheung et al, 2015;Custodio et al, 2019) or the reference standard (Goudsmit et al, 2018).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Translation and cultural adaption of the RUDAS Thirteen studies reported on procedures for translation and cultural adaption of the original Australian version of the RUDAS. In 10 studies (Ayan et al, 2019;Chaaya et al, 2016;Chen et al, 2015;de Araujo et al, 2018;Goudsmit et al, 2018;Iype et al, 2006;Limpawattana et al, 2012a;Nielsen et al, 2013;2019c;Shaaban et al, 2013), the RUDAS was translated from English into the target language (including Brazilian Portuguese, Chinese, classical Arabic, Danish, Dutch, French, German, Greek, Malay, Malayalam, Norwegian, Swedish, Thai, and Turkish) using translation-back-translation procedures but without making any cultural adaptation. Three studies reported cultural adaption of the RUDAS.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations